Interfacial Voids Trigger Carbon-Based, All-Inorganic CsPbIBr2 Perovskite Solar Cells with Photovoltage Exceeding 1.33 V - Zhu, Weidong; Zhang, Zeyang; Chen, Dandan; Chai, Wenming; Chen, Dazheng; Zhang, Jincheng; Zhang, Chunfu; Hao, Yue (Nano-Micro Letters, 2020)
A novel interface design is proposed for carbon-based, all-inorganic CsPbIBr2 perovskite solar cells (PSCs) by introducing interfacial voids between TiO2 electron transport layer and CsPbIBr2 absorber. Compared with the general interfacial engineering strategies, this design exempts any extra modification layer in final PSC. More importantly, the interfacial voids produced by thermal decomposition of 2-phenylethylammonium iodide trigger three beneficial effects. First, they promote the light scattering in CsPbIBr2 film and thereby boost absorption ability of the resulting CsPbIBr2 PSCs. Second, they suppress recombination of charge carriers and thus reduce dark saturation current density (J0) of the PSCs. Third, interfacial voids enlarge built-in potential (Vbi) of the PSCs, awarding increased driving force for dissociating photo-generated charge carriers. Consequently, the PSC yields the optimized efficiency of 10.20% coupled with an open-circuit voltage (Voc) of 1.338 V. The Voc achieved herein represents the best value among CsPbIBr2 PSCs reported earlier. Meanwhile, the non-encapsulated PSCs exhibit an excellent stability against light, thermal, and humidity stresses, since it remains 97% or 94% of its initial efficiency after being heated at 85 °C for 12 h or stored in ambient atmosphere with relative humidity of 30–40% for 60 days, respectively. Highlights: 1 A novel interface design of producing interfacial voids is proposed for CsPbIBr2 perovskite solar cells (PSCs), which is free of any extra modification layer. 2 Interfacial voids improve absorption of CsPbIBr2 film, reduce saturation current density, and enlarge built-in potential of the PSCs. 3 The PSC yields a superior efficiency of 10.20% with a record-high photovoltage of 1.338 V.